Road salt induced mobilization and accumulation of heavy metals in roadside bioretention in the field: the roles of season, plant uptake, media, and catchment properties - Bhabishya Khaniya; Christopher Szota; Tim D. Fletcher; Jennifer Drake (Chemosphere, 2026)

The Black Array of Broadband Absolute Radiometers Earth Radiation Imager: Science Requirements, Instrument Design, and Concept of Operations - Odele Coddington; Cameron Straatsma; Ginger Drake; Kush Tyagi; Michelle Stephens; Chris Yung; Nathan Tomlin; John Lehman; Chip Bollendonk; Paris Buedel; Katherine Catani; Beth Cervelli; et al. (Advances in Atmospheric Sciences, 2026)
The Black Array of Broadband Absolute Radiometers Earth Radiation Imager (BABAR-ERI) is a small, adaptable nadir-pointed pushbroom imager to measure Earth-leaving broadband radiance from 0.3 µm to 100 µm with higher information content than is currently measured by reducing radiometric uncertainty and enabling cloud-resolving spatial resolution. The three-instrument BABAR-ERI suite fits a 12U CubeSat form factor and contains co-registered science telescope channels for measuring shortwave (0.3 µm to 4.5 µm band) and total radiance (0.3 µm to 100 µm band), dual-channel on-board radiance stability monitors, and a visible-wavelength camera. Novel, 1 × 32 element, electrical-substitution radiometer pixels image the shortwave and total radiance in 1 km × 1 km co-registered ground footprints; longwave radiance (4.5 µm to 100 µm band) is derived from subtraction of the shortwave and total radiance. The dual-channel onboard stability monitors are radiance standard detectors, and their measurements, acquired concurrently with the science telescopes and at much different duty cycles for the dual channels, will be used to track and correct the degradation of the science channels. The single-channel, mid-visible camera facilitates geolocation pointing knowledge and provides scene context information and sub-pixel variability to facilitate measurement stability studies and enable process-level science studies at high spatial resolution. The detectors for the science channels and stability monitors are absolute, ambient-temperature, micro-fabricated, electrical-substitution radiometers with near-perfect optical absorptance across the measurement range from vertically aligned carbon nanotubes. The BABAR-ERI science channels will be characterized over the full measurement range and for variable Earth scenes and deep space temperatures during extensive ground calibrations.

Road salt reduces plant cover in bioretention systems within road rights-of-way - Bhabishya Khaniya; Christopher Szota; Tim D. Fletcher; Jennifer Drake (Science of The Total Environment, 2025)

Pavement wear generates microplastics in stormwater runoff - Kelsey Smyth; Shuyao Tan; Tim Van Seters; Vimy Henderson; Elodie Passeport; Jennifer Drake (Journal of Hazardous Materials, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Fruit and seed traits of native and invasive plant species in Hawai‘i: implications for seed dispersal by non-native birds - Jinelle H. Sperry; Dylan O’Hearn; Donald R. Drake; Amy M. Hruska; Samuel B. Case; Jeferson Vizentin-Bugoni; Clint Arnett; Tim Chambers; Corey E. Tarwater (Biological Invasions, 2021)

New innovations for 2018 and beyond - Tim Coulson; Peter Thrall; Jon Chase; Helmut Hillebrand; Vanessa Ezenwa; John Drake; Nathalie Espuno; Stephane Hello (Ecology Letters, 2018)

The marine cytotoxin portimine is a potent and selective inducer of apoptosis - Sarah L. Cuddihy; Sarah Drake; D. Tim Harwood; Andrew I. Selwood; Paul S. McNabb; Mark B. Hampton (Apoptosis, 2016)

Transformation of Althaea officinalis L. by Agrobacterium rhizogenes for the production of transgenic roots expressing the anti-HIV microbicide cyanovirin-N - Pascal M. W. Drake; Luisa de Moraes Madeira; Tim H. Szeto; Julian K-C. Ma (Transgenic Research, 2013)

Building local environmental knowledge in undergraduates with experiential wilderness skills and awareness training: the case of environmental sentinels - Jacob C. Brenner; Jason G. Hamilton; Tim Drake; Jed Jordan (Journal of Environmental Studies and Sciences, 2013)

GIS and multiple-criteria evaluation for the optimisation of tsetse fly eradication programmes - Elias Symeonakis; Tim Robinson; Nick Drake (Environmental Monitoring and Assessment, 2007)